Design of a Solar Power System for a Four-Way Intersection Traffic Light Based on Time Scheduling Using PLC - Huda, Abil; Muis Prasetia, Abdul; Sartika, Linda (Universitas Muhammadiyah Surakarta, 2025)
Indonesia possesses significant potential for renewable energy utilization, particularly solar energy, with an average daily solar irradiance of 1,200 W/m². This condition is ideal for the development of Solar Power Plants (PLTS). On the other hand, traffic light systems, although critical for regulating vehicle flows, often rely on fixed time cycles that are inefficient under varying traffic volumes. To address this issue, an adaptive control system based on a Programmable Logic Controller (PLC) is proposed, utilizing a time scheduling method. During the evening rush hour from 16:00 to 17:00, the total traffic light cycle duration is 199 seconds, distributed as follows: the South direction experiences a 147-second wait with 48 seconds of green light, the North waits for 165 seconds with 30 seconds of green light, the East waits for 166 seconds with 29 seconds of green light, and the West waits for 120 seconds with 75 seconds of green light. The yellow light is active for 3 seconds in all directions, and there is a 1-second red light buffer before transitioning between intersections